Effect of functional electric stimulation on phonation in an ex vivo aged ovine model - Jakubaß, Bernhard; Peters, Gregor; Kniesburges, Stefan; Semmler, Marion; Kirsch, Andrijana; Gerstenberger, Claus; Gugatschka, Markus; Döllinger, Michael (Journal of the Acoustical Society of America, 2023)
With age, the atrophy of the thyroarytenoid muscle (TAM), and thus atrophy of the vocal folds, leads to decreased glottal closure, increased breathiness, and a loss in voice quality, which results in a reduced quality of life. A method to counteract the atrophy of the TAM is to induce hypertrophy in the muscle by functional electric stimulation (FES). In this study, phonation experiments were performed with ex vivo larynges of six stimulated and six unstimulated ten-year-old sheep to investigate the impact of FES on phonation. Electrodes were implanted bilaterally near the cricothyroid joint. FES treatment was provided for nine weeks before harvesting. The multimodal measurement setup simultaneously recorded high-speed video of the vocal fold oscillation, the supraglottal acoustic signal, and the subglottal pressure signal. Results of 683 measurements show a 65.6% lower glottal gap index, a 22.7% higher tissue flexibility (measured by the amplitude to length ratio), and a 473.7% higher coefficient of determination (R2) of the regression of subglottal and supraglottal cepstral peak prominence during phonation for the stimulated group. These results suggest that FES improves the phonatory process for aged larynges or presbyphonia.
CRIS-Team Scopus Importer:2023-05-19